2015
DOI: 10.1063/1.4936200
|View full text |Cite
|
Sign up to set email alerts
|

Shaping symmetric Airy beam through binary amplitude modulation for ultralong needle focus

Abstract: Needle-like electromagnetic field has various advantages for the applications in high-resolution imaging, Raman spectroscopy, as well as long-distance optical transportation. The realization of such field often requires high numerical aperture (NA) objective lens and the transmission masks. We demonstrate an ultralong needle-like focus in the optical range produced with an ordinary lens. This is achieved by focusing a symmetric Airy beam (SAB) generated via binary spectral modulation with a digital micromirror… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…It is observed that the curved main lobe of AB is not broken by the obstacle, except at its neighborhood, confirming its self-healing feature. Our simulations provide evidence that the SAB also presents a self-healing characteristic supporting preliminary results obtained in [28]. In fact, notice that the main symmetric specular lobes are not affected by the perturbation except at its neighborhood.…”
Section: Theoretical Resultssupporting
confidence: 76%
“…It is observed that the curved main lobe of AB is not broken by the obstacle, except at its neighborhood, confirming its self-healing feature. Our simulations provide evidence that the SAB also presents a self-healing characteristic supporting preliminary results obtained in [28]. In fact, notice that the main symmetric specular lobes are not affected by the perturbation except at its neighborhood.…”
Section: Theoretical Resultssupporting
confidence: 76%
“…In contrast, the 0th-order Bessel-Gaussian beam shows a needle-like structure near the focus (Figure 2F). Such needle-like focus structure could also be created by other types of non-diffracting beams like the symmetric Airy beam (SAB) [42].…”
Section: Bessel and Airy Beamsmentioning
confidence: 99%
“…symmetric CPM to produce the SAB [42]. Broadband polarization-insensitive operation of the DMD allows the modulation of light from the ultraviolet to near-infrared spectrum.…”
Section: Spatial Light Modulatormentioning
confidence: 99%
“…In order to verify these findings, the creation of APPB is implemented through a digital micromirror device (DMD). The advantage of DMD is its capability to present the diffractive patterns with a considerably fast speed 32 . Entire modulation over the complex amplitude modulation is achieved through binary amplitude holograms designed by a super-pixel algorithm 33 .…”
Section: Introductionmentioning
confidence: 99%